PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN LINGKUNGAN KERJA FISIK TERHADAP KINERJA KARYAWAN PT.TARAINDO ENERGI PERKASA - Andri Setiawan; Shela Indah Savitri (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
This study examines the transformational leadership style and physical work environment on employee performance at PT. Taraindo Energi Perkasa, both partially and simultaneously. Employing a quantitative associative approach, it processes questionnaire data via SPSS version 23. The population comprises 60 employees, serving as the sample. Analysis techniques include instrument tests, classical assumption tests, regression, correlation coefficients, determination coefficients, and hypothesis testing. Findings reveal transformational leadership style positively and significantly impacts employee performance partially, with t-calculated (6.529) > t-table (2.002) and significance of 0.424 (42.4%), rejecting H0 and accepting Ha. The physical work environment also exerts a positive significant partial effect, t-calculated (6.305) > t-table (2.002), with 0.422 (42.2%) significance, accepting Ha and rejecting H0. Simultaneously, both variables positively and significantly affect performance, yielding the regression equation: Y = 1.951 + 0.469X1 + 0.466X2. F-calculated (45.824) > F-table (3.10), with 0.617 (61.7%) significance, rejecting H0 and accepting Ha. Recommendations urge leaders to adapt approaches, enhance lighting, and refine work programs and job descriptions to boost employee performance at PT. Taraindo Energi Perkasa.